Assessment of renal function - Raimann, Jochen (Henry Stewart Talks, 2016)
Progress in understanding and methodologies for assessing renal function, Physiology of glomerular filtration as the main marker of renal function, Assessment of glomerular filtration rate using various methods, Simplified methods allowing quantification of glomerular filtration rate